Efficacy and safety of multiple intra-articular corticosteroid injections for osteoarthritis—a systematic review and meta-analysis of randomized controlled trials and observational studies. (12th January 2021) - Ayub, Shazeen; Kaur, Jaspreet; Hui, Michelle; Espahbodi, Shima; Hall, Michelle; Doherty, Michael; Zhang, Weiya
Abstract: Objectives: To investigate the efficacy and safety of multiple intra-articular corticosteroid (IACS) injections for the treatment of OA. Methods: We conducted electronic searches of several databases for randomized controlled trials (RCTs) and observational studies. Standard mean difference was calculated for efficacy, whereas hazard ratio (HR) was used for adverse effects. Results were combined using the random effects model. Heterogeneity was measured using I 2 statistics. Results: Six RCTs were included for efficacy assessment. The use of multiple IACS appeared to be better than comparator (standard mean difference for pain −0.47, 95% CI −0.62, 0.31). However, there was considerable heterogeneity ( I 2 92.6%) and subgroup analysis by comparator showed no separation of regular IACS from placebo, though timing of pain assessments was questionable. Fourteen RCTs and two observational studies were assessed for the safety of multiple IACS. Minor local adverse events were similar in both groups. One RCT found that regular IACS every 3 months for 2 years caused greater cartilage loss compared with saline injection (−0.21 vs 0.10 mm). One cohort study found that multiple IACS injections associated with worsening of joint space narrowing (HR 3.02, 95% CI 2.25, 4.05) and increased risk of joint replacement (HR 2.54, 95% CI 1.81, 3.57). Conclusion: Multiple IACS injections are no better than placebo for OA pain according to current evidence. The preliminary finding of a detrimental effect on structural OA progression warrants further investigation. Efficacy and safety of multiple IACS reflecting recommended best practice has yet to be assessed.